Words at Work: Constructing a Labour Conflict - Reshef, Yonatan; Keim, Charles (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2016)
SummaryWe use the 2011-12 conflict between the British Columbia Teachers’ Federation (BCTF) and the British Columbia (BC) government to explore how the union president, Susan Lambert, used language to bring the conflict into being and mobilize union members in opposition to the government. We use newspaper articles and archival material from mid-2011 to June 2012 to explore how Lambert identified the core issues and actors, prescribed roles, relationships and actions, and, importantly, inspired a will to act in union members and supporters.To explore how she constructed the conflict, we adopt a mobilization theory developed by scholars of social movement organizations (SMO). Snow and Benford (1988: 200-202) conceptualize three core pillars of conflict: 1- diagnostic framing identifies a problem, attributes blame or causality, and identifies the key actors; 2- prognostic framing offers a solution and identifies strategies, tactics and targets; 3- motivational framing provides a call to arms, or rationale for action while inspiring an urge to act among members and supporters. In exploring how she urged action among members, we use the four archetypal legitimation strategies identified by Van Leeuwen (2008) and Van Leeuwen and Wodak (1999): authorization, rationalization, moralization and mythopoesis.McAdam (1982: 48) argues that before collective action can begin people must come to view their situation as unjust and subject to change. We use the above framework to structure our exploration of how the union president used language to frame members’ understanding of the conflict. Through language she ushered the reality of labour conflict into being and constructed a reality in which union members could identify themselves as agents of protest and change.